Application of QSAR models to the search for tubulin inhibitors in a series of derivatives of 1,3-oxazole - Semenyuta, I.V.; Kovalishyn, V.V.; Pilyo, S.G.; Blagodatnyy, V.N.; Trokhimenko, Е.P.; Brovarets, V. S.; Metelitsa, L.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The study shows the usage of QSAR models for the search for new tubulin inhibitors. The activity of 282 potential tubulin inhibitors on a dataset of 978 derivatives of oxazole and thiazole is predicted. The calculated Tanimoto index value was 0.5–0.76 for 127 compounds, which confirms the similarity of the structures in the training and test sets. The cytotoxic effect of 11 most active compounds was studied on the cell culture Hep-2. Compounds 1, 3, and 4 showed a high activity with LD50 125.0, 31.7, and 62.5 mg/ml, respectively. Their maximum tolerated doses (MTD) are found to be 15.8, 15.8, and 31.7 mg/ml, respectively. The established LD50 and MTD of compounds 1, 3, and 4 allow us to recommend them for the further study as potential anticancer agents.